Systematic review of the impact of patient death on surgeons. Issue 11 (2nd August 2019) - Joliat, G-R; Demartines, N; Uldry, E
Abstract: Background: The death of a patient is experienced at some time by most surgeons. The aim of this review was to use existing literature to establish how surgeons have dealt with the death of patients. Methods: A systematic review of the medical literature was performed. MEDLINE/PubMed, Ovid, Web of Science, Embase, and Google Scholar were searched for qualitative and quantitative studies on surgeon reactions when facing death or a dying patient. This systematic review was performed following the recommendations of the Cochrane collaboration and reported following the PRISMA guidelines. Individual and interview-based opinions were summarized and synthesized. Results: An initial search found 652 articles. After exclusion of articles that did not satisfy the inclusion criteria, 20 articles remained and seven were included. Two of these articles were personal opinion of the author and five were interviews or surveys. The main findings were that facing death routinely induces a strong psychological burden and that surgeons are more at risk than the general population to develop psychological morbidity. Conclusion: Although it is a frequent and emotional subject in the surgical world, the impact of patient death on surgeons is not abundantly studied in the literature. Dealing with patient death or taking care of a dying patient might have long-lasting psychological impact on surgeons. Graphical Abstract: The present manuscript reviewed the existing literature on how surgeons react to and face the death of a patient. Seven articles were included in this review, summarized and discussed. Most of them were related to psychological burden and impact throughout a surgeon's life. Significant impact that is understudied